Weightlifting sport for all sports - Urso, A. (Calzetti & Mariucci Publishers, 2011)
One of the peculiar characteristics of weightlifting is that as time goes by, athletes experience "rejuvenation". This rejuvenation is mainly due to the fact that, in addition to being a noble Olympic sport, it is one of the best training systems for all types of sports that require considerable amounts of strength. It is precisely for this research into training, which is adopted in numerous sports, that this first volume has fully elaborated the subject by illustrating every aspect of Olympic and auxiliary exercises: from biomechanical references, to the problems of teaching and learning and general parameters of periodisation. Additionally, much attention was given to the aspects of body composition and functional rehabilitation which by means of weightlifting exercises provide an excellent base for all sports. CHAPTER 1 - WEIGHTLIFTING. PAST AND PRESENT 1.1 The origins of weightlifting 1.2 The technical-stylistic evolution of weightlifting 1.3 The reason behind the categories 1.4 Women`s weightlifting CHAPTER 2 - QUALITATIVE BIOMECHANICAL ANALYSIS OF OLYMPIC WEIGHTLIFTING 2.1 Means and limits 2.2 Qualitative biomechanical models of olympic exercises 2.3 Technical considerations from a mechanical viewpoint CHAPTER 3 - WEIGHTLIFTING TECHNIQUES 3.1 General remarks 3.2 The barbell trajectory in the first and second pull 3.3 The trajectory in the jerk 3.4 Dynamics and kinematics in the snatch and clean & jerk 3.5 Dynamics and kinematics of the jerk CHAPTER 4 - USING THE BARBELL 4.1 The grip 4.2 The pitch CHAPTER 5 - TYPES OF EXERCISES 5.1 Competition exercises: the snatch 5.2 The clean & jerk: the clean 5.3 The jerk 5.4 Auxiliary exercises for the snatch 5.5 Auxiliary exercises for the jerk: competition exercises 5.6 Auxiliary exercises for the jerk 5.7 Exercises to develop specific strength in the snatch 5.8 Exercises to develop specific strength in the clean and jerk CHAPTER 6 - MAIN TECHNICAL FAULTS AND HOW TO CORRECT THEM 6.1 Conditions that favour faults 6.2 The most frequent and important faults 6.3 Cause of faults in the snatch 6.4 Cause of the fault in the clean 6.5 Cause of the error in the jerk 6.6 Analyses of the possible causes of incorrect or incomplete movements CHAPTER 7 - TRAINING THE TECHNIQUE. LEARNING THE TECHNIQUE 7.1 Training the technique 7.2 Learning the technique 7.3 Learning in evolution 7.4 Teaching principles 7.5 Steps to be followed CHAPTER 8 - GENERAL PROGRAMMING ELEMENTS OF MODERN WEIGHTLIFTING 8.1 Programming 8.2 Structure of the training session 8.3 Structure of the macrocycle 8.4 Structure of the mesocycle 8.5 Structure of the microcycle 8.6 Classification of microcycles CHAPTER 9 - TEACHING OLYMPIC EXERCISES 9.1 Snatch 9.2 Clean & jerk CHAPTER 10 - EVALUATION OF A SPORTS TECHNIQUE CHAPTER 11 - SIMILARITIES BETWEEN WEIGHTLIFTING EXERCISES AND MAIN SPORTS MOVEMENTS 11.1 The concept of biomechanical similarities between exercises and various sports movements 11.2 Similarities with main sports movements CHAPTER 12 - WEIGHTLIFTING FOR OTHER SPORTS 12.1 Introduction 12.2 Ontogenetic development of physical abilities 12.3 Table on the use of weightlifting in various sports 12.4 The use of weights in cyclic sports 12.5 The use of weights in acyclic sports 12.6 Weights in mixed sports 12.7 The use of weights in situation sports CHAPTER 13 - BODY COMPOSITION IN WEIGHTLIFTING 13.1 Studying body composition 13.2 Tricompartmental model 13.3 Our experience with italian olympic athletes CHAPTER 14 - INJURIES IN WEIGHTLIFTING 14.1 Introduction 14.2 Knee injuries 14.3 Spine pathologies 14.4 Shoulder pathologies 14.5 Recommended therapies for weightlifting pathologies